Designing Pricing Contracts for Boundedly Rational Customers: Does the Framing of the Fixed Fee Matter? - Ho, Teck-Hua; Zhang, Juanjuan (Management Science, 2008)
The format of pricing contracts varies substantially across business contexts, a major variable being whether a contract imposes a fixed fee payment. This paper examines how the use of the fixed fee in pricing contracts affects market outcomes of a manufacturer-retailer channel. Standard economic theories predict that channel efficiency increases with the introduction of the fixed fee and is invariant to its framing. We conduct a laboratory experiment to test these predictions. Surprisingly, the introduction of the fixed fee fails to increase channel efficiency. Moreover, the framing of the fixed fee does make a difference: an opaque frame as quantity discounts achieves higher channel efficiency than a salient frame as a two-part tariff, although these two contractual formats are theoretically equivalent. To account for these anomalies, we generalize the standard economic model by allowing the retailer's utilities to be reference dependent so that the up-front fixed fee payment is perceived as a loss and the subsequent retail profits as a gain. We embed this reference-dependent utility function in a quantal response equilibrium framework where the retailer is allowed to make decision mistakes due to computational complexity. The key prediction of this behavioral model is that channel efficiency decreases with loss aversion for sufficiently Nash-rational retailers. Consistent with this prediction, the estimated loss-aversion coefficient is 1.37 in the two-part tariff condition, significantly higher than 1.27 in the quantity discount condition. At the same time, loss aversion dominates contract complexity in explaining the data. Lastly, we conduct a follow-up experiment to confirm the central role of loss aversion as a behavioral driver. In one condition, the retailer becomes less loss averse when we temporally compress the fixed fee payment and the realization of retail profits, which supports the loss aversion theory. In the other condition, the retailer's contract acceptance rate does not decline when we reward the manufacturer a higher cash payment for each experimental point earned, which rules out the competing hypothesis that the retailer rejects contract offers due to fairness concerns.